Sharia Fiscal Instruments in Combating Inflation: A Conceptual Case Study Based on Classical and Modern Islamic Economic Literature - Abu Lubaba; Fitri Faujiah (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
Inflation is a major economic challenge that erodes purchasing power, widens income inequality, and disrupts economic stability. From an Islamic economic perspective, inflation is not merely a monetary phenomenon but is also tied to wealth distribution, economic justice, and the strengthening of the real sector, so Islamic economics offers various Sharia fiscal instruments capable of supporting inflation control while improving social welfare. This study aims to analyze the role of Sharia fiscal instruments in addressing inflation based on classical and contemporary Islamic economic perspectives. It employs a descriptive qualitative approach using library research, drawing on secondary data from classical Islamic literature, journal articles, academic books, and official institutional reports, analyzed through content analysis and strengthened by source triangulation. The findings indicate that zakat, infaq, sadaqah, productive waqf, kharaj, and public asset management play a strategic role in economic stability: zakat, infaq, and sadaqah function as income-redistribution mechanisms that protect the purchasing power of low-income groups, while productive waqf and public asset management enhance real-sector productivity and reduce supply-side pressures. These instruments also strengthen fiscal resilience. The study implies that optimally implemented Sharia fiscal instruments can serve as an effective alternative policy promoting price stability, economic equity, and welfare consistent with Maqashid al-Shariah.